The African food crisis : lessons from the Asian Green Revolution - Djurfeldt, Göran, 1945- (CABI Pub., 2005)
This book is the outcome of a three-year project coordinated by a group of Swedish researchers and with collaborating scholars from Africa and Asia. It provides a comparative study between Asian agricultural development during the Green Revolution in food production and the current problematic agricultural situation in sub-Saharan Africa.